Noncoding RNAs Act as Tumor-Derived Molecular Components in Inducing Premetastatic Niche Formation - Zhang, Zhedong (Biomed Res Int, 2019)
Cancer metastasis has been demonstrated as it is the culmination of a cascade of priming steps. Increasing evidence has shown that tumor-derived molecular components (TDMCs) are known as extra cellular vesicle and nonvesicle factors and serve as versatile intercellular communication vehicles which can mediate signaling in the tumor microenvironment while creating the premetastatic niche. Noncoding RNAs (ncRNAs) as one of the TDMCs have been proved in participating in the formation of the premetastatic niche. Understanding the premetastatic niche formation mechanisms through TDMCs, especially ncRNAs may open a new avenue for cancer metastasis therapeutic strategies. In this review, recent findings regarding ncRNAs function were summarized, and then the interaction with the premetastatic niche formation was studied, which highlight the potential of using ncRNAs for cancer diagnosis and therapeutic effect.